The clinical utility of serum uric acid measurement in pre-eclampsia - M a j e e d, B u s h r a M . (Journal of the Faculty of Medicine Baghdad, 2007)
Background:To evaluate the accuracy of serum uric acid to predict maternal and fetal complications in women with pre- eclampsia. Design: Prospective study. Setting: Tikrit Teaching Hospital. Subject and Methods: Fifty normotensive and forty-three pre-eclamptic pregnant women at (20-24) weeks of gestation were the study subject, serum concentrations of uric acid were measured and examine the correlations between serum uric acid level with fetal and maternal complications. Result: Serum concentration of uric acid in pre-eclamptic women were significantly higher than in gestational age match normotensive pregnant women, and women with pre-eclampsia and elevated uric acid concentration at increased risk of low birth weight , preterm delivery and cesarean , delivery compared with each condition in absence of hyperuricemia. Conclusion: Hypervricemia consider a good predictor to select group of per-eclamptic women with high risk for fetal and maternal complications.